Geometric Programming with Discrete Variables Subject to Max-Product Fuzzy Relation Constraints - Zejian Qin; Bingyuan Cao; Shu-Cherng Fang; Xiao-Peng Yang (Discrete Dynamics in Nature and Society)
The problem of geometric programming subject to max-product fuzzy relation constraints with discrete variables is studied. The major difficulty in solving this problem comes from nonconvexity caused by these product terms in the general geometric function and the max-product relation constraints. We proposed a 0-1 mixed integer linear programming model and adopted the branch-and-bound scheme to solve the problem. Numerical experiments confirm that the proposed solution method is effective.